1966
DOI: 10.1002/jcp.1040670410
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinetics of antibody formation

Abstract: The mediastinal nodes of untreated rats contain medullary cords populated by variously matured plasmocytes, classified into large, medium, and small on the basis of nuclear diameters. Since hemocytopoietic cells proliferate while maturing and since proliferation yields progressively greater numbers of mitoses, it follows that the order of mitotic increment of the variously matured plasmocytes can tell the position of each type in the plasmocytic series. Counts were carried out in 32 rats killed at four success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1969
1969
1971
1971

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Similar studies showed that uridine incorporation is reduced to less than 10 0/0 of the 5 day level, while leucine incorporation diminished much less markedly. This is similar to the pattern of macromolecular synthesis seen in other erythropoietic systems (Grasso and Woodard, 1965, 1966, 1967Kovach et al ., 1967 ;de la Chapelle et al ., 1969) . Our analysis will deal only with the primitive line of red cells .…”
Section: Cell Cycle Analysissupporting
confidence: 84%
“…Similar studies showed that uridine incorporation is reduced to less than 10 0/0 of the 5 day level, while leucine incorporation diminished much less markedly. This is similar to the pattern of macromolecular synthesis seen in other erythropoietic systems (Grasso and Woodard, 1965, 1966, 1967Kovach et al ., 1967 ;de la Chapelle et al ., 1969) . Our analysis will deal only with the primitive line of red cells .…”
Section: Cell Cycle Analysissupporting
confidence: 84%
“…The cell which gives rise to the plasma cell is not absolutely identified. Four contenders theft have been considered are lymphatic reticular cells (19 21), lymphocytes (22)(23)(24), endothelial cells in the postcapillary venules of lymphatic tissue (25), and perivascular mesenchymal cells (26). The ancestral cell, not necessarily the immediate parent cell, is assumed to be a mobile cell of the bone marrow, for imnmnoglobulins of allogeneic radiation chimeras are of the donor type (27).…”
Section: Discussionmentioning
confidence: 99%